1984
DOI: 10.1007/bf01654932
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid autografts—morphology and function: Six years' experience with parathyroid autotransplantation in uremic patients

Abstract: Recurrence of hyperparathyroidism (HPT) following total parathyroidectomy and autotransplantation (APTX) has been reported before. However, no data about the time interval between grafting and relapse and about morphology were given. Only 1 case of primary hyperparathyroidism with APTX has been extensively analyzed. We have performed autotransplantation in 42 patients with HPT due to chronic renal failure. Implanted parathyroid tissue showed typical chief cell hyperplasia. Within 4–33 months, 6 patients develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
1
16
1
3
Order By: Relevance
“…Although no graft reimplantation is performed after intramuscular autograftectomy, repeated autograftectomy may indicate incomplete autograftectomy because of the locally invasive behavior of the intramuscular transplanted cells and the difficulty in distinguishing the grafted parathyroid tissue from the surrounding muscle. 13 In contrast, the only repeated autograftectomy in the Subcutaneous group was caused by hyperplasia of the preserved autograft, rather than local recurrence in the cleaned pockets.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although no graft reimplantation is performed after intramuscular autograftectomy, repeated autograftectomy may indicate incomplete autograftectomy because of the locally invasive behavior of the intramuscular transplanted cells and the difficulty in distinguishing the grafted parathyroid tissue from the surrounding muscle. 13 In contrast, the only repeated autograftectomy in the Subcutaneous group was caused by hyperplasia of the preserved autograft, rather than local recurrence in the cleaned pockets.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies reported the high incidence of intramuscular autograftectomy and repeated autograftectomy without comparison with subcutaneous autografts. [13][14][15] Chou et al 16 reported intramuscular autotransplantation had a greater incidence of autograftectomy than subcutaneous autotransplantation (9 of 75, 12% vs 1 of 110, 0.9%). The present study shows that intramuscular parathyroid autotransplantation led to a greater incidence of autograftectomy (15 of 65, 23% vs 14 of 823, 1.7%) and repeated autograftectomy (4 of 65, 6.4% vs 1 of 823, 0.1%) than subcutaneous parathyroid autotransplantation.…”
Section: Discussionmentioning
confidence: 96%
“…4,5). Im Gesamtkrankengut wurden ü ber 60 % der hiervon betrof-fenen Patienten innerhalb von 4 Wochen beschwerdefrei, wä hrend sich das ossä re Syndrom lä ngerfristig zurü ckbildete.…”
Section: Ergebnisseunclassified
“…Replantiertes nodulä r-hyperplastisches Nebenschilddrü sengewebe fü hrt in hö herem Maße zum Rezidiv als diffus-hyperplastisches Gewebe [3,13,14]. Obwohl bei 2 unserer Patienten mit Transplantatrezidiv bis zur neuerlichen Normalisierung der Transplantatfunktion je 2 Revisionen erforderlich waren, beobachteten wir keinwie von anderen Autoren beschrieben [5] -infiltratives Wachstum des transplantierten Nebenschilddrü sengewebes. Obwohl bei 2 unserer Patienten mit Transplantatrezidiv bis zur neuerlichen Normalisierung der Transplantatfunktion je 2 Revisionen erforderlich waren, beobachteten wir keinwie von anderen Autoren beschrieben [5] -infiltratives Wachstum des transplantierten Nebenschilddrü sengewebes.…”
Section: Ergebnisseunclassified
“…with thyroid cancer, since lymph node dissection jeopardizes the vascularity of parathyroid glands leading to postoperative hypoparathyroidism [3]. Although the results of autotransplantation are satisfactory in most cases, problems such as the recurrence of hyperparathyroidism due to graft hyperplasia or hypoparathyroidism due to failure of autotransplanted normal parathyroid gland to function does occur in a few cases [4][5][6].…”
mentioning
confidence: 99%